Factors Predicting Sustained Implementation of a Universal Behavior Support Framework. (June 2018) - McIntosh, Kent; Mercer, Sterett H.; Nese, Rhonda N. T.; Strickland-Cohen, M. Kathleen; Kittelman, Angus; Hoselton, Robert; Horner, Robert H.
In this 3-year prospective study, we tested the extent to which school-, practice-, and district-level variables predicted sustained implementation for schools in various stages of implementation of school-wide positive behavioral interventions and supports (SWPBIS) Tier 1 (universal) systems. Staff from 860 schools in 14 U.S. states completed a research-validated measure of factors associated with sustained implementation of school interventions during Year 1 of this study. Analyses included multigroup structural equation modeling of school and district implementation fidelity data. Results indicated that adequate implementation fidelity and better Team Use of Data for decision making in Study Year 1 were the strongest predictors of sustained implementation in Year 3. In addition, the number of other schools in the district adopting SWPBIS was a similarly strong predictor. A critical mass of schools implementing was also predictive, especially for schools earlier in implementation. School characteristics were not predictive, except for grade levels served, which was an inconsistent predictor by stage.